Biomarker research to improve clinical outcomes of peritoneal dialysis: consensus of the European Training and Research in Peritoneal Dialysis (EuTRiPD) network - Aufricht, Christoph; Schmitt, Claus P. (Kidney international, 2017)
Peritoneal dialysis (PD) therapy substantially requires biomarkers as tools to identify patients who are at the highest risk for PD-related complications and to guide personalized interventions that may improve clinical outcome in the individual patient. In this consensus article, members of the European Training and Research in Peritoneal Dialysis Network (EuTRiPD) review the current status of biomarker research in PD and suggest a selection of biomarkers that can be relevant to the care of PD patients and that are directly accessible in PD effluents. Currently used biomarkers such as interleukin-6, interleukin-8, ex vivo-stimulated interleukin-6 release, cancer antigen-125, and advanced oxidation protein products that were collected through a Delphi procedure were first triaged for inclusion as surrogate endpoints in a clinical trial. Next, novel biomarkers were selected as promising candidates for proof-of-concept studies and were differentiated into inflammation signatures (including interleukin-17, M1/M2 macrophages, and regulatory T cell/T helper 17), mesothelial-to-mesenchymal transition signatures (including microRNA-21 and microRNA-31), and signatures for senescence and inadequate cellular stress responses. Finally, the need for defining pathogen-specific immune fingerprints and phenotype-associated molecular signatures utilizing effluents from the clinical cohorts of PD patients and "omics" technologies and bioinformatics-biostatistics in future joint-research efforts was expressed. Biomarker research in PD offers the potential to develop valuable tools for improving patient management. However, for all biomarkers discussed in this consensus article, the association of biological rationales with relevant clinical outcomes remains to be rigorously validated in adequately powered, prospective, independent clinical studies.
Available online 8 August 2017
Gesehen am 28.08.2018